2018
DOI: 10.1016/j.jval.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Patient-Reported Outcome Measure for Geriatric Care: The Older Persons and Informal Caregivers Survey Short Form

Abstract: Background: The Older Persons and Informal Caregivers Minimum Data Set (TOPICS-MDS) is a standardized data set that was developed to evaluate the quality of multidimensional geriatric care. There is an inherent need to reduce the number of TOPICS-MDS survey items to core outcomes to allow it to be more easily applied as a patient-reported outcome measure in clinical settings. Objectives: To create a TOPICSshort form (TOPICS-SF) and examine its validity. Methods: Data in the TOPICS-MDS from persons aged 65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Fifteen studies reported the mean age for caregivers that ranged from 44 years to 70 years . Clinical populations under investigation were stroke survivors and their caregivers in 21 studies (21/23 [91%]) . Two studies investigated older people admitted to the hospital, irrespective of medical diagnosis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies reported the mean age for caregivers that ranged from 44 years to 70 years . Clinical populations under investigation were stroke survivors and their caregivers in 21 studies (21/23 [91%]) . Two studies investigated older people admitted to the hospital, irrespective of medical diagnosis .…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome measure was patient HRQOL. This is justified given the reported importance of patient HRQOL as a meaningful outcome shared by both patient and caregiver . Secondary outcome measures included caregiver HRQOL, caregiver burden, patient function, patient and caregiver anxiety and depression, adverse events (including falls, delirium, medical complications, delayed hospital discharge, and emergency department/hospital readmission), and cost effectiveness/health resource utilization.…”
Section: Methodsmentioning
confidence: 99%
“…TOPICS-SF is a newer instrument designed to assess physical and mental health and quality of life in the elderly, for use in evaluating patient-reported outcomes in geriatric care. 43 TOPICS-SF includes questions on general health, pain, cognitive function, mood, activities of daily living and social activities.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire results are used to generate a Frailty Index (FI), which is calculated as the summation of the values associated with each answer, divided by the total of answered questions. The feasibility, validity, and reliability of the instrument as a frailty questionnaire has been established in previous studies [ 24 , 25 ]. It has also been validated as a PROM [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has also been validated as a PROM [ 23 ]. The TOPICS-SF is currently accepted by the Dutch Geriatrics Society as a PROM for older patients throughout the Netherlands, and it is being implemented within several hospitals throughout the country [ 25 ]. The TOPICS-SF is included in Multimedia Appendix 2 .…”
Section: Methodsmentioning
confidence: 99%